The suppression of manganese superoxide dismutase decreased the survival of human glioblastoma multiforme T98G cells (Faculty of Medicine Universitas Indonesia, 2017)
Background: Glioblastoma multiforme (GBM) is a primary malignant brain tumor which has poor prognosis. High incidence of oxidative stress-based therapy resistance could be related to the high antioxidant status of GBM cells. Our previous study has reported that manganese superoxide dismutase (MnSOD) antioxidant expression was significantly higher in high grade glioma than in low grade. The aim of this study was to analyze the impact of MnSOD suppression toward GBM cell survival.Methods: This study is an experimental study using human glioblastoma multiforme T98G cell line. Suppression of MnSOD expression was performed using in vitro transfection MnSOD-siRNA. The MnSOD expression was analyzed by measuring the mRNA using real time RT-PCR, protein using ELISA technique, and specific activity of enzyme using inhibition of xantine oxidase. Concentration of reactive oxygen species (ROS) intracellular was determined by measuring superoxide radical and hydrogen peroxide. Cell survival was analyzed by measuring viability, proliferation, and cell apoptosis.Results: In vitro transfection of MnSOD-siRNA suppressed the mRNA, protein, and specific activity of MnSOD. This treatment significantly increased the concentration of superoxide radical; however, it did not influence the concentration of hydrogen peroxide. Moreover, viability MnSOD-suppressing cell significantly decreased, accompanied by increase of cell apoptosis without affecting cell proliferation.Conclusion: The suppression of MnSOD expression leads to decrease glioblastoma multiforme cell survival, which was associated to the increase of cell apoptotic.